2023
DOI: 10.3390/brainsci13040574
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Corticospinal Tract Homology of Faremus Personalized Neuromodulation Relieving Fatigue in Multiple Sclerosis: A Proof-of-Concept Study

Abstract: Objectives: Fatigue in multiple sclerosis (MS) is a frequent and invalidating symptom, which can be relieved by non-invasive neuromodulation, which presents only negligible side effects. A 5-day transcranial direct-current stimulation, 15 min per day, anodically targeting the somatosensory representation of the whole body against a larger occipital cathode was efficacious against MS fatigue (fatigue relief in multiple sclerosis, Faremus treatment). The present proof-of-concept study tested the working hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…We note that in that intervention, the targets of neuromodulation were left vs. right primary sensorimotor homologs, whereas bilateral alterations are typically observed in task-specific focal dystonia (Melgari et al, 2013 ; Dresel et al, 2014 ), suggesting the appropriateness of a bilateral intervention. On this basis, we believe that the proposed S1 neuromodulation (Tecchio et al, 2014 ; Cancelli et al, 2018 ) can offer a promising therapeutic enrichment, inducing bilateral rather than unilateral facilitation, and focusing the facilitatory effects on somatosensory rather than sensorimotor areas supporting the physiological sensorimotor integration processing (Porcaro et al, 2019 ; Padalino et al, 2021 ; Bertoli et al, 2023 ).…”
Section: Point Of View For Discussion Of a New Multidimensional Thera...mentioning
confidence: 99%
“…We note that in that intervention, the targets of neuromodulation were left vs. right primary sensorimotor homologs, whereas bilateral alterations are typically observed in task-specific focal dystonia (Melgari et al, 2013 ; Dresel et al, 2014 ), suggesting the appropriateness of a bilateral intervention. On this basis, we believe that the proposed S1 neuromodulation (Tecchio et al, 2014 ; Cancelli et al, 2018 ) can offer a promising therapeutic enrichment, inducing bilateral rather than unilateral facilitation, and focusing the facilitatory effects on somatosensory rather than sensorimotor areas supporting the physiological sensorimotor integration processing (Porcaro et al, 2019 ; Padalino et al, 2021 ; Bertoli et al, 2023 ).…”
Section: Point Of View For Discussion Of a New Multidimensional Thera...mentioning
confidence: 99%
“…Recent findings show that as right-hand dominance increases, the similarity in the homologous corticospinal tracts’ recruitment patterns also increases ( Pagliara et al, 2023 ). Furthermore, a neuromodulation intervention relieving chronic fatigue normalized these inter-lateral balances ( Bertoli et al, 2023 ). This underscores the potential of using resting-state indices to evaluate hemispheric homology, particularly for chronic symptom management.…”
Section: Discussionmentioning
confidence: 99%
“…The inter-hemispheric balance is crucial in chronic conditions such as fatigue ( Cogliati Dezza et al, 2015 ; Ondobaka et al, 2022 ), and it influences the severity of stroke ( Deco and Corbetta, 2011 ; Pellegrino et al, 2012 ; Zappasodi et al, 2014 ; Soleimani et al, 2023 ) and aging ( Cottone et al, 2013 ). In particular, neuromodulation interventions aimed at relieving fatigue have been observed to restore the physiological homology of primary motor areas ( Porcaro et al, 2019 ) and of the cortico-spinal tracts ( Bertoli et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous trials have shown promising results on the efficacy of Faremus ( Tecchio et al, 2016 ; Cancelli et al, 2018b ). Recently, the authors reached an average improvement in fatigue levels of 27%, which is considered clinically significant ( Bertoli et al, 2023 ). The ongoing adaptation and personalized nature of Faremus allow for long-term effectiveness and the potential to explore fatigue re-emergence over time.…”
Section: State-of-the-art In Personalized Neurostimulationmentioning
confidence: 99%
“…Moreover, personalized neurostimulation interventions have revealed alterations in neural connectivity as Faremus-induced neurostimulation have been demonstrated to have an impact in the connectivity between dominant and non-dominant corticospinal tracts. This emphasized the specific effect that personalized interventions can have on an individual’s neural connectivity and organization ( Porcaro et al, 2019 ), highlighting the importance of tailoring treatments to target the central nervous system in conditions such as MS fatigue ( Bertoli et al, 2023 ).…”
Section: State-of-the-art In Personalized Neurostimulationmentioning
confidence: 99%